Cohesión social y satisfacción con la colonia: estudio en comunidades urbanas de ingreso medio-bajo - Ibarra Salazar, Jorge; Salazar Cantú, José de Jesús; Navarro Aguirre, Rafael (El Colegio de México A.C., 2023)
In this paper the relationship of social cohesion and neighborhood satisfaction, an indicator of welfare of residents, is analyzed. Using data of a survey applied to residents of two neighborhoods in Monterrey, Nuevo Leon, considering different attributes of the social environment (neighborhood trust, neighborhood participation, collaborative behavior, and neighborhood identity), we calculate an index of social cohesion to relate with neighborhood satisfaction. We estimated different specifications by probit and ordered probit. We find evidence that social cohesion has a positive and statistically significant relationship with the degree of neighborhood satisfaction. This result not only contributes to the related literature, but also to validate social programs and public policy whose objective is to increase the well-being of citizens through actions aimed at improving social cohesion.